2018
DOI: 10.18632/oncotarget.24488
|View full text |Cite
|
Sign up to set email alerts
|

Merestinib (LY2801653) inhibits neurotrophic receptor kinase (NTRK) and suppresses growth of NTRK fusion bearing tumors

Abstract: Merestinib is an oral multi-kinase inhibitor targeting a limited number of oncokinases including MET, AXL, RON and MKNK1/2. Here, we report that merestinib inhibits neurotrophic receptor tyrosine kinases NTRK1/2/3 which are oncogenic drivers in tumors bearing NTRK fusion resulting from chromosomal rearrangements. Merestinib is shown to be a type II NTRK1 kinase inhibitor as determined by x-ray crystallography. In KM-12 cells harboring TPM3-NTRK1 fusion, merestinib exhibits potent p-NTRK1 inhibition in vitro by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 29 publications
(48 reference statements)
0
22
0
1
Order By: Relevance
“…Although designed to be an inhibitor of MET, merestinib also inhibits the receptor tyrosine kinases MST1R, AXL, ROS1, PDGFRA, FLT3, TEK, DDR1, DDR2, MERTK, TYR03, TRKA, TRKB, and TRKC , as well as the serine/threonine kinases MKNK1 and MKNK2 . This property may explain the occasional observed responses in the few patients with tumor regression in our study.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although designed to be an inhibitor of MET, merestinib also inhibits the receptor tyrosine kinases MST1R, AXL, ROS1, PDGFRA, FLT3, TEK, DDR1, DDR2, MERTK, TYR03, TRKA, TRKB, and TRKC , as well as the serine/threonine kinases MKNK1 and MKNK2 . This property may explain the occasional observed responses in the few patients with tumor regression in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Merestinib (LY2801653), developed initially to target the MET kinase, is an oral kinase inhibitor with antitumor proliferative and antiangiogenic activity in MET‐amplified and MET autocrine xenograft tumor models . Merestinib is also active against other receptor tyrosine kinases (MST1R [RON], AXL, ROS1, PDGFRA, FLT3, TEK, DDR1, DDR2, MERTK, TYR03, TRKA, TRKB, and TRKC) and serine/threonine kinases (MKNK1 and MKNK2) . Recent studies demonstrated merestinib inhibits MKNK1‐ and MKNK2‐induced phosphorylation of eukaryotic translation initiation factor 4E and may represent a unique approach to treatment of acute myeloid leukemia or tumors with mitogen‐activated protein kinase pathway activation .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the aforementioned inhibitors, many others have been validated in solid tumors bearing NTRK fusions or mutations. These include cabozantinib [109], foretinib [109], merestinib [110], and nintedanib [109] among others. Moreover, IGF1R/IR pathway inhibitors, in particular, have shown to be effective at blocking EN activity by initiating a process that results in the ubiquitylation and proteasomal degradation of the fusion protein itself [96].…”
Section: Ntrk Inhibition In Hematological Malignanciesmentioning
confidence: 99%
“…Развитие лекарственной устойчивости описано и при применении других ИТК. Для преодоления резистентности в настоящее время проводятся клинические исследования I-II фазы ИТК 2-го поколения, таких как селитректиниб (selitrectinib, Loxo-195), репотректиниб (repotrectinib; TPX-0005 в исследовании TRIDENT-1), мерестиниб (merestinib, LY2801653) [24]. [25] с разрешения авторов) Fig.…”
Section: Introductionunclassified